2004
DOI: 10.4161/cbt.3.7.965
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenesis and activation of Wnt signaling by bone morphogenetic protein 4 in human cancer cells

Abstract: Aberrations in BMP signaling have recently been implicated as a cause of human cancer. Here we demonstrate and define the tumor suppressive properties of BMP4. Consistent with its potential role in a tumor suppressor pathway, BMP4 treatment eliminated the tumorigenic potential of an undifferentiated human cancer cell line. This loss of tumorigenicity was accompanied by an increase in apoptosis, alterations in cell cycle profile, and an increase in cell size. Interestingly, human colon cancer cells were resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 23 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…S1 B ). The mRNA level of Smad7 was unchanged in the tested cells (Supplementary Table S5) and no genes associated with the induction of BMP signaling were observed (18). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1 B ). The mRNA level of Smad7 was unchanged in the tested cells (Supplementary Table S5) and no genes associated with the induction of BMP signaling were observed (18). …”
Section: Resultsmentioning
confidence: 99%
“…Our Western experiments showed that SMAD7 is expressed uniformly and at much higher levels than SMAD6 in both normal and cancer cells derived from the lung but is induced to a much less extent on TGF-β and BMP stimulation (data not shown). Similarly, down-regulation of SMAD6 by shRNA did not affect the expression of Smad7 or affected genes commonly involved in BMP induction (18). …”
Section: Discussionmentioning
confidence: 99%
“…Both Wnt and BMP pathways were initially selected after the findings of Nishanian et al [34], who demonstrated the interaction between these two pathways. Both pathways were thoroughly investigated through the Cancer Genome Anatomy Project site [35], but we failed to find any information regarding the BMP pathway in either this or other web browsers.…”
Section: Methodsmentioning
confidence: 99%
“…Both pathways were thoroughly investigated through the Cancer Genome Anatomy Project site [35], but we failed to find any information regarding the BMP pathway in either this or other web browsers. For that reason, Wnt genes were selected by browsing the pathway through Biocarta [36], whereas BMP genes had to be strictly selected from previous literature [17], [34]. Forty-one genes were finally selected to be included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A similar positive interaction was also observed between rs17563 on BMP4 and smoking for CRC risk in a previous study [ 47 ] in spite of little linkage disequilibrium between rs1957636 and rs17563 (r 2 = 0.12 in HapMap3 JPT + CHB + CHD individuals). Biologically, BMP signaling has been suggested to cause human cancer through its tumor suppressor properties, but colon cancer cells were resistant to the growth suppression and differentiation induced by BMP4 [ 48 ]. Experiments conducted using a rat model showed that BMP4 was up-regulated by chronic cigarette smoking [ 49 ].…”
Section: Discussionmentioning
confidence: 99%